PENGELOLAAN PAJAK PERTAMBAHAN NILAI PADA TRANSAKSI PENJUALAN (STUDI KASUS : PT ELSISCOM PRIMA KARYA JAKARTA) - Kamal, Fahmi; Ruliyan, Rio (FEB Universitas Sam Ratulangi Manado, 2019)
The Tax Invoice issued by the seller is used as proof of levies on the payable VAT that must be deposited in each Tax Period to the State Treasury. With this state policy, it is expected that PT Elsiscom Prima Karya Jakarta as a corporate taxpayer will become more aware and support the target of tax revenue for the continuity of the country's development and implementation. The data that the authors obtained in this study are 2017 and 2018. The type of research and data collection techniques used are by conducting field research in the form of observations, interviews, and documentation, literature review and other supporting information. The purpose of this study is to determine the management of Value Added Tax on sales transactions and reporting of Value Added Tax in companies that are in accordance with the provisions of Law Number 18 of 2000 concerning Value Added Tax. The results of the authors obtained in this study are PT Elsiscom Prima Karya Jakarta has contributed to the state in implementing Value Added Tax for each business activity and in sales transactions which is one of the tax obligations that must be carried out by the company